2017
DOI: 10.1002/jhet.2907
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Some New Ciprofloxacin Hybrids as Potential Antimicrobial Agents

Abstract: A new series of ciprofloxacin hybrid compounds as new type of antimicrobial agents were synthesized and evaluated for antibacterial activity against Gram‐positive and Gram‐negative bacteria.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 24 publications
0
11
0
Order By: Relevance
“…Also it was found that 1,2,4‐triazole‐5(4 H )‐one/thione ciprofloxacin hybrids 39 and 40 bearing substituted piperazine at the C‐3 position of triazole moiety displayed promising in vitro activity against all tested Gram‐positive and Gram‐negative pathogens with MIC < 0.24 μg/mL which was far more potent than ampicillin (MIC: 3.9–250 μg/mL) . Further investigation of hybrids 41 indicated 1,2,4‐triazole‐5(4 H )‐thione motif affected the antibacterial activity greatly against the tested pathogens including drug resistant strains; phenyl groups especially electron‐donating phenyl groups at C‐3 position of 1,2,4‐triazole‐5(4 H )‐thione motif were vital for the excellent antibacterial activity, and the shorter alkyl in N‐4 position preferred the activity . In particular, hybrid 41 with MIC ranging from 0.01 to 1.32 μg/mL showed balanced activity against Gram‐positive and Gram‐negative drug‐sensitive and drug‐resistant bacteria .…”
Section: Recent Advances Of Quinolone Antibacterial Agentsmentioning
confidence: 97%
See 1 more Smart Citation
“…Also it was found that 1,2,4‐triazole‐5(4 H )‐one/thione ciprofloxacin hybrids 39 and 40 bearing substituted piperazine at the C‐3 position of triazole moiety displayed promising in vitro activity against all tested Gram‐positive and Gram‐negative pathogens with MIC < 0.24 μg/mL which was far more potent than ampicillin (MIC: 3.9–250 μg/mL) . Further investigation of hybrids 41 indicated 1,2,4‐triazole‐5(4 H )‐thione motif affected the antibacterial activity greatly against the tested pathogens including drug resistant strains; phenyl groups especially electron‐donating phenyl groups at C‐3 position of 1,2,4‐triazole‐5(4 H )‐thione motif were vital for the excellent antibacterial activity, and the shorter alkyl in N‐4 position preferred the activity . In particular, hybrid 41 with MIC ranging from 0.01 to 1.32 μg/mL showed balanced activity against Gram‐positive and Gram‐negative drug‐sensitive and drug‐resistant bacteria .…”
Section: Recent Advances Of Quinolone Antibacterial Agentsmentioning
confidence: 97%
“…Further investigation of hybrids 41 indicated 1,2,4‐triazole‐5(4 H )‐thione motif affected the antibacterial activity greatly against the tested pathogens including drug resistant strains; phenyl groups especially electron‐donating phenyl groups at C‐3 position of 1,2,4‐triazole‐5(4 H )‐thione motif were vital for the excellent antibacterial activity, and the shorter alkyl in N‐4 position preferred the activity . In particular, hybrid 41 with MIC ranging from 0.01 to 1.32 μg/mL showed balanced activity against Gram‐positive and Gram‐negative drug‐sensitive and drug‐resistant bacteria . Addition of naphthyridinone into C‐3 position of 1,2,4‐triazole‐5(4 H )‐thione moiety 42 also showed promising antibacterial activity with MIC in a range of <1.0–9.7 μg/mL, which was more potent than ampicillin (MIC: 10–>128 μg/mL).…”
Section: Recent Advances Of Quinolone Antibacterial Agentsmentioning
confidence: 99%
“…Minimal inhibitory concentration assay (MIC, µg/mL) was conducted to scan the susceptibility of some bacterial strains to the newly synthesized compounds. 26,27 The MIC assays for bacteria were done in LB medium at pH 7.2. Dimethyl sulfoxide (DMSO) was used to dissolve the compounds to prepare stock solutions.…”
Section: Anti-microbial and Anti-fungal Activitymentioning
confidence: 99%
“…1,2 Plech et al reported several series of ciprofloxacin-1,2,4-triazole-5(4H)-thione hybrids 1, where R 1 is phenyl and R 2 is mainly phenyl or benzyl group, respectively, and some of the hybrids were more potent than the parent ciprofloxacin against the tested pathogens. [15][16][17][18] The SAR studies indicated that the substituents at C-3 position of 1,2,4-triazole-5(4H)-thione motif have great influence on the antibacterial activity, and phenyl ring is indispensable for the excellent antibacterial activity; For N-4 position of the 1,2,4triazole-5(4H)-thione moiety, the length of alkyl substituent plays a pivotal role in the antibacterial activity, and shorter alkyl substituent preferred.…”
Section: Introduction *mentioning
confidence: 99%